Pemetaan Potensi Pariwisata Berbasis Komunitas Melalui Eksplorasi Keunikan Seribu Pantai di Malang Selatan - M. R. Khairul Muluk; Dessanti P.S. Ari; Latifah Hanum (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2020)
Identifying tourist attractions in each local area needed to exploring the uniqueness of potential to each tourist attraction, and the identification result used for both visitors and residents. The problem of rural development tourism is identifying uniqueness from tourist attractions. It has an impact on visitors who are not easy to find a unique destination of beach attractions in Malang Regency. This study employs a rapid rural appraisal (RRA). RRA appears especially relevant for identification and appraisal. Information is needed quickly and decisions are preempted by the passage of time. As a result, uniqueness identification is used to developing each beach attractions in Malang Regency, and every actor involved in developing tourist destinations can improve the management elements and infrastructure that do not yet exist.